CD4+CXCR3+ T cells and plasmacytoid dendritic cells drive accelerated atherosclerosis associated with systemic lupus erythematosus. (September 2015) - Clement, Marc; Charles, Nicolas; Escoubet, Brigitte; Guedj, Kevin; Chauveheid, Marie-Paule; Caligiuri, Giuseppina; Nicoletti, Antonino; Papo, Thomas; Sacre, Karim
Abstract: Cardiovascular disease due to accelerated atherosclerosis is the leading cause of death in patients with systemic lupus erythematosus (SLE). Noteworthy, accelerated atherosclerosis in SLE patients appears to be independant of classical Framingham risk factors. This suggests that aggravated atherosclerosis in SLE patients may be a result of increased inflammation and altered immune responses. However, the mechanisms that mediate the acceleration of atherosclerosis in SLE remain elusive. Based on experimental data which includes both humans (SLE patients and control subjects) and rodents (ApoE−/− mice), we herein propose a multi-step model in which the immune dysfunction associated with SLE (i.e. high level of IFN-α production by TLR 9-stimulated pDCs) is associated with, first, an increased frequency of circulating pro inflammatory CD4+CXCR3+ T cells; second, an increased production of CXCR3 ligands by endothelial cells; third, an increased recruitment of pro-inflammatory CD4+CXCR3+ T cells into the arterial wall, and fourth, the development of atherosclerosis. In showing how SLE may promote accelerated atherosclerosis, our model also points to hypotheses for potential interventions, such as pDCs-targeted therapy, that might be studied in the future. Highlights: Lupus immunopathogenesis accelerates atherosclerosis. pDCs and CD4+ T cells are part of a chemokine-based positive feedback circuit involved in SLE-associated atherosclerosis. Blockade of pDCs may constitute a therapeutic strategy to limit the development of atherosclerosis in SLE patients.